Enhancing the diagnosis of sublingual sialolith using CBCT: a case report - Putra, Dimas Satria; Epsilawati, Lusi (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: This case report was created to provide further insight into the use of CBCT in detecting sialolith lesions. Case Report: A 27-year-old female patient was referred to the radiology department of Padjadjaran University Dental Hospital for CBCT radiograph examination related to complaints of swelling in the right lingual area of the mandible and pain. The results of the radiograph examination analysis showed irregular, well-defined radiopaque, in the lingual area of regio 44-45, measuring 34.31 mm2, and the lesion was not associated with the mandible. Intra-oral examination revealed irregular swelling and the same color as the lingual mucosa of regio 44-45. The analysis showed that the lesion was located in the salivary duct of the sublingual area and the patient was diagnosed with sublingual sialolithiasis dextra. Conclusion: CBCT analysis can be used to accurately identify the position, quantity, and morphology of sialoliths and interpret their three-dimensional positioning in relation to adjacent structures.